Resistance integrons. Mini review - Fariba Akrami; Mahdi Rajabnia; Abazar Pournajaf (Babol University of Medical Sciences, 2019)
Integrons are a segment of dsDNA that play a major role in bacterial adaptation and evolution. These genetic determinants are known by the presence of three necessary apparatuses: an integrase (intI gene), Pc (a promoter) and attI (a recombination site). These elements are able to acquire gene cassettes, which can carry antibiotic resistance factors, via site-specific recombination mechanism. The most common types of resistance integrons are class I (Tn402 derivatives), followed by class II and III. In recent years, the role of integrons as an important factor in the transmission and spread of resistance factors has been considered. Therefore, the ongoing threats posed by integrons require an understanding of their origins and evolutionary history. This review examines the functions and activities of integrons. It shows how antibiotics use selected particular integrons from the environmental pool, so that integrons carrying resistance genes are now present in the majority of Gram-negative pathogens.